The Effect of Thickness on Strength of Single Lap Orbital Riveted Aluminum/Composite Joints Used in Marine Environments - Guido Di Bella; Tiziana Alderucci; Federica Favaloro; Chiara Borsellino (Metals, 2022)
In an innovative vision of manufacturing, orbital riveting is a joining technique characterized by high efficiency, energy saving, low costs and low noise. It is a cold forming process where a tool rotates at a fixed angle (i.e., typically 3° to 6°) to create a sweeping line of pressure around a rivet. This movement progressively promotes, with each rotation, the collapse of the rivet shank down onto the upper substrate of a joint, permanently forming a rivet head. The aim of this research is to make and test multi-material joints between an aluminum AA5083 H111 sheet and a glass fiber reinforced laminate. Specifically, nine configurations of single lap joints were studied by investigating the effect of the thickness (i.e., 2.5, 3.0 and 4.0 mm for the aluminum and 2.5, 3.0 and 4.0 mm for the composite laminate) both on the mechanical characteristics and on the failure modes.